Identifying key traits in high-yielding rice cultivars for adaptability to both temperate and tropical environments - Takai, Toshiyuki; Lumanglas, Patrick; Simon, Eliza Vie; Arai-Sanoh, Yumiko; Asai, Hidetoshi; Kobayashi, Nobuya (Elsevier, 2019)
Increasing rice yield potential is a continuous challenge posed by world population growth. To increase yield potential, favorable alleles of valuable genes need to be accumulated in promising germplasm. We conducted comparative yield trials for two years in Tsukuba, Japan, in a temperate region and at the International Rice Research Institute (IRRI), Philippines, in a tropical region using five high-yielding rice cultivars: Takanari and Hokuriku193, developed in Japan, and IR64, NSIC Rc158, and YTH183, developed in the Philippines. Genotype plus genotype × environment interaction (GGE) biplot analysis across four environments (two regions × two seasons) classified the five cultivars into four categories: Takanari and YTH183 showed high adaptability to both tropical and temperate regions, Hokuriku193 was suitable for temperate regions, NSIC Rc158 was suitable for the tropics, and IR64 was inferior to the other cultivars in both regions. The high yield and adaptability in Takanari and YTH183 were attributed to their large sink capacity with good grain filling. The plant type for high yield was different, however, between the two cultivars; Takanari was a panicle-weight type, whereas YTH183 was a panicle-number type. Evaluations of F2 progeny of a cross between Takanari and YTH183 showed transgressive segregation for number of panicles per plant as well as number of spikelets per panicle, leading some F2 plants to produce more spikelets per plant (corresponding to larger sink size) than the parental cultivars in both regions. These results suggest the possibility of developing rice cultivars with high yield potential in both temperate and tropical regions by crossing temperate with tropical high-yielding cultivars